Evaluation of the Safety, Tolerability, and Pharmacokinetics of GSK2269557 (Nemiralisib) Administered Via Dry Powder Inhaler to Healthy Japanese Subjects. Issue 1 (10th October 2018) - Ino, Hiroko; Wilson, Robert; Terao, Takumi; Ogura, Hirofumi; Igarashi, Harue; Cahn, Anthony; Numachi, Yotaro
Abstract: The aim of the study was to assess the safety, tolerability, and pharmacokinetics of single and repeat doses of nemiralisib administered via a dry powder inhaler to healthy Japanese subjects. This was a single‐center, double‐blind, randomized, placebo‐controlled, parallel, single‐ and repeat‐ascending‐dose study. Thirty‐six healthy Japanese male subjects were randomized to receive either 1 dose strength of nemiralisib or placebo. The study consisted of a screening period, a single‐dose session (session 1), a repeat‐dose session (session 2), a 10‐day washout period between the sessions, and then a follow‐up visit 10 ± 1 days after the last dose of session 2. No serious adverse events were reported. No clinically significant abnormalities were found in clinical laboratory results, vital signs, or spirometry results. Generally, exposure (maximum observed plasma concentration [Cmax ] and area under the concentration‐time curve [AUC]) increased with dose in an approximately proportional manner. Plasma Tmax was achieved rapidly at approximately 0.08 hours, and the terminal elimination half‐life (T1/2 ) was approximately 40 hours. Tmax and T1/2 did not change between days or doses in the single‐ and repeat‐dose sessions. Following 10 daily doses of 200, 500, and 700 μg nemiralisib, accumulation was observed, and the ratios (session 2, day 10:session 1) for Ro(AUC0‐24 ) and R(Cmax ) were 2.4‐3.0 and 1.5‐1.7, respectively. Steady state was achieved by 6‐7 days, based on trough observed plasma drug concentration (Ctrough ) values.